2015
DOI: 10.1002/jcu.22281
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography of the liver in children with Wilson's disease: Preliminary results

Abstract: In pediatric patients with WD, LS is high at the time of diagnosis and decreases during specific treatment, in parallel with an increase in the urinary copper concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…4 A few studies have demonstrated the potential of ultrasound (US) elastography and serologic markers as noninvasive monitoring modalities for WD. [5][6][7][8] Ultrasound elastographic techniques have been validated as accurate diagnostic tools for liver fibrosis. 9,10 However, because of the rarity of the disease, these techniques have not been widely researched in the context of WD, with only a few available studies [6][7][8] on transient elastography (TE) and acoustic radiation force impulse imaging.…”
mentioning
confidence: 99%
“…4 A few studies have demonstrated the potential of ultrasound (US) elastography and serologic markers as noninvasive monitoring modalities for WD. [5][6][7][8] Ultrasound elastographic techniques have been validated as accurate diagnostic tools for liver fibrosis. 9,10 However, because of the rarity of the disease, these techniques have not been widely researched in the context of WD, with only a few available studies [6][7][8] on transient elastography (TE) and acoustic radiation force impulse imaging.…”
mentioning
confidence: 99%
“…Trabut et al (15) showed that the Fibroscan value of 137 patients who were hospitalized for the purpose of giving up alcohol decreased from 7,2 kPa to 6,1 kPa only in 7 days on which the subjects did not drink alcohol. Stefanescu et al (16) showed that the Fibroscan values decreased with the copper chelation treatment in patients with Wilson's disease with no fibrosis. According to these studies, it is understood that the accumulation diseases in except to fibrosis also increases stiffness of the liver, and may be detected with Fibroscan.…”
Section: Discussionmentioning
confidence: 99%
“…However, both TE and APRI/FIB‐4 have been mostly validated for fibrosis staging in viral liver disease and in non‐alcoholic fatty liver disease . Data on non‐invasive methods to stage fibrosis in WD are scarce . After long discussions with Food and Drug Administration (FDA) and European Medicines Agency (EMA) it became clear that our armamentarium to predict the outcome of liver disease (ie surrogate endpoints) in WD is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,14 Data on non-invasive methods to stage fibrosis in WD are scarce. 15 After long discussions with Food and Drug Administration (FDA) and…”
Section: Introductionmentioning
confidence: 99%